Konflik Keluarga dalam Rumah Tangga Muda pada Film Dua Hati Biru Karya Gina S. Noer (Analisis Isi Kualitatif)) - Syuaramustdalifah, Asy; Hariyati, Farida; Pranawati, Rita (JOEAI (Journal of Education and Instruction), 2025)
This study aims to identify and analyze forms of family conflict in young households as portrayed in the film Dua Hati Biru by Gina S. Noer. Using a qualitative approach and content analysis method, this research focuses on scenes depicting interpersonal conflicts between a young married couple. The findings reveal that the conflicts include differences in parenting styles, economic pressure, interference from extended family, and a lack of effective communication. The film also portrays conflict resolution through open communication, compromise, and mutual understanding. The study highlights that family-themed films can serve as reflective and educational media regarding social realities. Furthermore, such films can be examined through the lens of family communication theory to deepen insights into relational dynamics within households.   Keywords:                   Family Conflict,          Young Marriage,            Content           Analysis,         Family Communication